1997
DOI: 10.1002/(sici)1097-0142(19971201)80:11<2120::aid-cncr11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Testicular "Tumor" of the adrenogenital syndrome

Abstract: This case illustrates an unusual presentation of a testicular tumor in a patient with the adrenogenital syndrome as well as with myelolipoma and seminoma in a cryptorchid testis. The possibility of an associated neoplasm that could be potentially fatal should be considered whenever a testicular tumor of the adrenogenital syndrome continues to grow despite adequate hormonal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…These lesions have been found in the liver, lung, mediastinum, mesentery, stomach, spleen, pelvis, and most commonly the retroperitoneal presacral region [4, 5]. Our review of the literature demonstrates there have been 45 reported cases of extra-adrenal myelolipomas, some with multiple lesions and locations including: 16 presacral, 9 retroperitoneal, 8 thoracic/mediastinal, 7 perirenal, 3 pelvic, 2 renal, 2 hepatic, 1 gastric, and 1 perivesicular [1, 623].…”
Section: Discussionmentioning
confidence: 99%
“…These lesions have been found in the liver, lung, mediastinum, mesentery, stomach, spleen, pelvis, and most commonly the retroperitoneal presacral region [4, 5]. Our review of the literature demonstrates there have been 45 reported cases of extra-adrenal myelolipomas, some with multiple lesions and locations including: 16 presacral, 9 retroperitoneal, 8 thoracic/mediastinal, 7 perirenal, 3 pelvic, 2 renal, 2 hepatic, 1 gastric, and 1 perivesicular [1, 623].…”
Section: Discussionmentioning
confidence: 99%